Formulation And Physical Evaluation Of Hand Sanitizer Gel Spray Gel Preparations From Aloe Vera Gel (Aloe vera L.) - Haryani, Reny; Nur Khotimah, Enis (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2023)
Hand Sanitizer is a hand sanitizer that has antibacterial ability in inhibiting and killing bacteria. Hand sanitizer spray is a spray-shaped hand sanitizer to clean or remove germs on hands containing active ingredients irgasan DP 300: 0.1% and alcohol 60%. This study aims to determine that aloe vera gel (Aloe vera L.) can be formulated into Hand Sanitizer gel spray preparations and physical evaluation of Hand sanitizer gel spray from aloe vera gel (Aloe vera L.) at concentrations of 8.5%, 10.5% and 12.5%. The formulation of the spray gel from aloe vera gel is carried out by formulating the active substance into an optimal base. The active substances added with concentrations vary, namely 8.5%, 10.5% and 12.5% then evaluated organoleptically, homogeneity, pH, and Hedonic. The dosage form of the spray gel is viscous, the spray gel has the aroma of citrus oil and its color is weak pink and strong pink. From the results of the physical evaluation of hand sanitizer spray gel preparations from aloe vera gel on organoleptic tests, homogeneity tests, pH tests and favorability tests, it shows that hand sanitizer spray gel preparations meet the requirements of a good spray gel. The results obtained from the hedonic test (favorability) showed that the 3rd formula containing the active substance aloe vera gel was most preferred with the most percentage results.